Midwifery students’ knowledge, understanding and experiences of workplace bullying, and violence: An integrative review - Simpson, N.; Wepa, D.; Vernon, R.; Briley, A.; Steen, Mary (2023)
Background: Workplace bullying, and violence within the midwifery profession, has been a well-documented concern in health literature since the early 1990′s. However, contemporary research highlights that workplace bullying, and violence is often inflicted upon midwifery students. Workplace bullying, and violence has both short- and long-term effects on the student, including psychological trauma and poor mental health, loss of passion for the midwifery profession and absenteeism. To consider a solution to this phenomenon, current literature regarding midwifery students’ knowledge, understanding and experiences of workplace bullying, and violence has been reviewed. Objective: To explore and critique current literature on midwifery students’ knowledge, understanding and experiences of workplace bullying, and violence. Design: An integrative review. Review methods: Toronto & Remington's six-stage systematic framework was used to conduct the review, with rigour and validity for the research process. Results: Following critical appraisal, 12 articles met the inclusion criteria. Four themes emerged: (1) Prevalence and types of workplace bullying, and violence towards midwifery students. (2) Impact of workplace bullying, and violence on midwifery students’ experiences during the degree. (3) Impact of negative workplace culture on the midwifery profession. (4) The requirement to develop strategies for midwifery students to address workplace bullying, and violence. Conclusions: Workplace bullying, and violence is a global health concern within the midwifery profession with evidenced impact on midwifery students’ professional and personal lives. Organisational systems and approaches were identified as causes of a toxic clinical environment and workplace bullying, and violence, which impacted midwifery students’ experiences. Suggestions supported universities incorporating conflict resolution strategies into midwifery degree programs, to prepare midwifery students to manage workplace bullying, and violence. Tweetable abstract: Workplace bullying, and violence is a global health concern entrenched within the midwifery profession, impacting midwifery students’ professional and personal lives. Incorporating conflict resolution strategies into Bachelor of midwifery degree programs, may help prepare midwifery students to manage workplace bullying, and violence.